ダイ39ジ ナンキョク チイキ カンソクタイ カキ コウドウ ホウコク 1997-1998 - 森脇, 喜一; モリワキ, キイチ; MORIWAKI, Kiichi (1998)
P(論文) 第39次南極地域観測隊(第39次隊)は1997年11月14日東京港を出発した。フリマントル寄港中に第38次越冬隊に緊急患者が発生したため昭和基地に直行し12月15日に到着した。患者収容と物資輸送後, 患者を送還するため「しらせ」はケープタウンまで往復した。「しらせ」は1月23日にアムンゼン湾トナー島に地学調査隊を送り込んだ後, 1月27日に昭和基地に戻った。昭和基地での建設等は12月中旬～2月中旬に行われた。昭和基地方面での野外調査は12月下旬～1月上旬と1月末～2月上旬にかけて, ドームふじ観測拠点への旅行は12月下旬～2月上旬になされた。大気採集実験は1月3日に実施された。第39次夏隊と第38次越冬隊は2月15日に昭和基地を離れ, 海底地形測量の後, 2月下旬にアムンゼン湾地域での観測を実施した。3月1日アムンゼン湾発, 同21日シドニー入港, 同28日, 空路成田に帰着した。海洋観測は東京からシドニーまでの「しらせ」航路上で実施した。 The 39th Japanese Antarctic Research Expedition (JARE-39) consisted of forty members of the wintering party and eighteen members of the summer party. The summer party was accompanied by other six persons including a guest scientist from Australia. JARE-39 left Tokyo on 14 November 1997 by the icebreaker SHIRASE, and arrived at Fremantle, Western Australia on 28 November. At Fremantle, JARE-39 received news of an emergency illness in the JARE-38 wintering party at Syowa Station, therefore JARE-39 hastened to the station, arriving on 15 December. After accommodating the invalid on board the SHIRASE, 1020t of cargo for the station was unloaded by 31 December, then several broken machines from the station were loaded by 5 January 1998,the SHIRASE left the station on 6 January to transport the invalid and a medical doctor of JARE-38 to Cape Town, South Africa. She returned to the station on 27 January via Tonagh Island, Amundsen Bay, where she arrived on 23 January and geological field work was carried out until 20 February. Construction to replace old buildings and facilities at Syowa Station was carried out from 16 December until 13 February. Geological, geophysical and biological field work, a micrometeorite search and geodesic surveys around Lutzow-Holm Bay, using helicopters on board the SHIRASE, were carried out between 18 December and 7 January, and between 27 January and 10 February. An oversnow traverse to and from Dome Fuji Station (77°19′S, 39°42′E, 3810m a.s.l.) was carried out from 23 December to 6 February. Atmospheric work using a cryogenic sampler with a large balloon was ...